Improving the Delivery of High-Quality Cancer Care in Medically Underserved Communities: A Formative Evaluation Method. Issue 4 (14th October 2021) - Quinn, Doris; Jacobson, Joseph O.; Wong, Sandra L.; Wollins, Dana; Gilmore, Terry; Cunningham, Gene
Abstract : Background and Objectives: In 2015, the American Society of Clinical Oncology launched a new program: Improving Quality of Care in Underserved Communities with the overarching aim of serving patients with cancer who have traditionally had difficulty accessing the care they need. Cancer care requires intense coordination of complex services to provide safe, effective, timely, and equitable care. If chemotherapy and/or radiation is needed, patients must navigate a complex system of care many times, a formidable challenge for many disadvantaged patients. Many practices believe that these patients face such significant issues that it is almost impossible to provide high-quality care. A grant from the Stavros Niarchos Foundation allowed us to select 4 oncology practices serving high proportions of racial minorities and persons of low socioeconomic status to participate in the new American Society of Clinical Oncology program. The program had 2 objectives: (1) to improve the capacity and capability of the participating practices to provide evidence-based, high-quality care; and (2) to identify and disseminate lessons learned for improving quality of care among oncology practices serving underserved patients. Methods: The program leveraged existing programs including the Quality Oncology Practice Initiative, which is a national performance measurement and improvement program that collects data about processes of care provided in the outpatient medical oncology setting, and the American Society of Clinical Oncology Quality Training Program, which provides training in how to apply the tools and methods of quality improvement in routine care settings. Training was provided in face-to-face and virtual meetings and participants were provided mentors throughout the program. At the conclusion, a formative evaluation method was used to assess whether the goals had been achieved. Objectives, activities, and desired outcomes were identified for each of the goals and thus became the framework for the evaluation. Results: The program met the stated goals and objectives. The evaluation revealed many successes, some surprises, and a list of improvements that were incorporated in the next iteration of this program. Based on data from the evaluation, the Niarchos Foundation provided funds for an additional 10 practices to participate in a similar program in 2020. Conclusion: This article outlines the evaluation of a new program demonstrating that medical oncology practices can make improvements in the care of their underserved populations if provided with the proper tools, methods, and coaching. The use of formative evaluation methodology also identified opportunities for improvement and ultimately resulted in additional funding for more practices to participate in the program.